Negotiation Strategy in The International Research Collaboration - Sri Wahyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
Negotiation is one of the endeavours undertaken by academic institutions in Indonesia to enhance their bargaining position, aiming to optimize the performance of scholarly publications as the primary outcome in international research collaborations. The success of these negotiations is significantly influenced by the strategies employed and the contributions offered to potential collaboration partners. In addition to strategic considerations, the proficiency in drafting Memoranda of Understanding (MOUs) and Technical Agreements is equally crucial in determining the outcomes of the negotiation process. This study examines the negotiation strategy undertaken by Indonesian partner institutions and its positive impact on scientific publication performance. The research adopts a qualitative approach. Primary data were collected through structured in-depth interviews using purposive method. Risk management analysis has been applied as theoretical framework to explain the implementation of research partnership carried out by Indonesian partner institutions. This study is considered important to provide a policy recommendation for Indonesian partner institutions.